The jurisdictional protection of the creditor - Vidal Ramírez, Fernando (2008)
The creditor has a fundamental right, the right to be paid. Article 1219 of the Civil Code legislates, as an effect of the obligations, the creditor's right to judicial protection if the debtor does not comply with them. The present study is dedicated to the interpretation of the mentioned Art. 1219º as it authorizes the creditor to make the jurisdictional trusteeship effective against his indebted one.